Sub-supercritical liquefaction of sugarcane bagasse for production of bio-oil and char: Effect of two solvents - Ahmed Baloch, H.; Nizamuddin, S.; Siddiqui, M.; Mujawar, Mubarak; Dumbre, D.; Srinivasan, M.; Griffin, G. (Elsevuer BV, 2018)
© 2018 Elsevier Ltd. This article aims investigating the solvo and hydrothermal liquefaction of sugarcane bagasse. Reaction temperature and solvents play an important role on the yield and physico-chemical properties of the liquefaction products. This study reports the effect of different temperatures, 240 °C, 260 °C and 280 °C and two different solvents, water and ethanol on yield and properties of bio-oil and char. The higher conversion was obtained at the higher temperatures with ethanol. The bio-oil yield ranged from 46.0% to 51.8% in presence of water and it ranged from 54.6% to 62.3% with ethanol solvent by changing reaction temperature from 240 °C to 280 °C. The char yield decreased from 36.3% to 28.2% and from 39.3% to 24.7% in presence of water and ethanol respectively by varying reaction temperature from 240 °C to 280 °C. The carbon content and HHV were increased and oxygen content was decreased in the products resulting in improved heating and combustion performance. The GC-MS results suggested that the all the bio-oils were mainly composed of phenols and its derivatives, alcohols, esters, hydrocarbons, ketones, aldehydes and other compounds. The TGA results proposed that the thermal stability of char was improved which is attributed to the reaction temperature of the liquefaction process.